A Single-Nucleotide Polymorphism in the Promoter of Porcine ARHGAP24 Gene Regulates Aggressive Behavior of Weaned Pigs After Mixing by Affecting the Binding of Transcription Factor p53 - Xu, Qinglei; Zhao, Jing; Guo, Yanli; Liu, Mingzheng; Schinckel, Allan P.; Zhou, Bo (Frontiers in Cell and Developmental Biology, 2022)
Pigs are an important biomedical model animals for the study of human neurological diseases. Similar to human aggressive behavior in children and adolescents, weaned pigs also show more aggressive behavior after mixing, which has negative effects on animal welfare and growth performance. Identification of functional single nucleotide polymorphisms (SNPs) related to aggressive behavior of pigs would provide valuable molecular markers of aggressive behavioral trait for genetic improvement program. Rho GTPase Activating Protein 24 (ARHGAP24) gene plays an important role in regulating the process of axon guidance, which may impact aggressive behavior of pigs. By re-sequencing the entire coding region, partially adjacent introns and the 5’ and 3’ flanking regions, 6 and 4 SNPs were identified in the 5’ flanking region and 5’ untranslated region (UTR) of porcine ARHGAP24 gene, respectively. Association analyses revealed that 9 SNPs were significantly associated with aggressive behavioral traits (P = < 1.00 × 10−4 - 4.51 × 10−2), and their haplotypes were significantly associated with aggressive behavior (P = < 1.00 × 10−4 - 2.99 × 10−2). The core promoter region of ARHGAP24 gene has been identified between -670 bp and -1113 bp. Furthermore, the luciferase activity of allele A of rs335052970 was significantly less than that of allele G, suggesting the transcriptional activity of ARHGAP24 gene was inhibited by allele A of rs335052970. It was identified that the transcription factor p53 bound to the transcription factor binding sites (TFBSs) containing allele A of rs335052970. In porcine primary neural cells, p53 bind to the target promoter region of ARHGAP24 gene, reduce its promoter transcriptional activity, and then reduce its messenger RNA (mRNA) and protein expression. The results demonstrated that ARHGAP24 gene had significant genetic effects on aggressive behavioral traits of pigs. Therefore, rs335052970 in ARHGAP24 gene can be used as a molecular marker to select less aggressive pigs.